Truncation of Kir6.2 produces ATP-sensitive K+ channels in the absence of the sulphonylurea receptor. - Tucker, S; Gribble, F; Zhao, C; Trapp, S; Ashcroft, F (1997)
ATP-sensitive potassium channels (K-ATP channels) couple cell metabolism to electrical activity and are important in the physiology and pathophysiology of many tissues. In pancreatic beta-cells, K-ATP channels link changes in blood glucose concentration to insulin secretion. They are also the target for clinically important drugs such as sulphonylureas, which stimulate secretion, and the K+ channel opener diazoxide, which inhibits insulin release. Metabolic regulation of K-ATP channels is mediated by changes in intracellular ATP and Mg-ADP levels, which inhibit and activate the channel, respectively. The beta-cell K-ATP channel is a complex of two proteins: an inward-rectifier K+ channel subunit, Kir6.2, and the sulphonylurea receptor, SUR1. We show here that the primary site at which ATP acts to mediate K-ATP channel inhibition is located on Kir6.2, and that SUR1 is required for sensitivity to sulphonylureas and diazoxide and for activation by Mg-ADP.